(untitled) (Journal of the College of Basic Education, 2023)
A person is considered a social being who tends to live among a specific group.security, stability and reassurance, and satisfy his need for belonging, and the person finds himself through thisBelonging There are many behaviors that reflect the social nature of man, and among theseBehaviors of cooperation, altruism, and social solidarity. Human relations are usually characterized byWith social cohesion, as well as there is a social attraction between individuals.Through these relationships, the individual acquires various social and moral standards.important psychological trends and learns how to behave in a social manner approved by the groupand accepted by the community. As the individual is transformed through this interaction from a child dependent on others.He is self-centered and aims in his life only to satisfy his physiological needs for a mature individual.He understands the meaning of social responsibility, and how to bear it, and knows the meaning of individuality and independence.self-reliant, able to control his emotions, and control the satisfaction of his needs in accordance withand social standards and realizes the values of society and adheres to them. And when he can’t evaluate this relationshipHis relationship with the members of the group is negatively affected, so he withdraws from them and lives in loneliness and isolation.Social isolation is a manifestation of human behavior.It has serious effects on the personality of the individual and his relationship with others, as it indicates his inability toto engage in social relations or to continue to be involved in themIn this case, he may separate himself from other people’s wives, which indicates insufficiency.Attractiveness of the network of social relations to the individual in terms of non-association between its members or alienationwith each other, with the absence of socially integrated relationships. This may be due to the rapid progresslife has witnessed recently, which contributed greatly to the spread of anxiety and depressionIn addition to the dissipation and alteration of many values, the disturbance of human relations and the feeling of insecurity.Psychologist (Mohammed, 2000, p. 193).The current research problem emerges from the nature of the sensitivity of the school stage (preparatory).Where the student is in a state of anxiety and tension, being the stage in which his future is determined.academic whether he entered the university or not. Therefore, the student here becomes in a state of distance fromothers, especially throughout the examination period, because he tries to achieve the highest possible level ofsuccess. And through what the researcher noticed during his visit to the schools in the period of applicationAnd supervising the students and what he heard from the school administrations in terms of observations about their students.Some of the students have cases in which they distance themselves from others. Therefore, the current study attempted